The Life of The Life of David Brainerd: Agency, Evangelicalism, and Book History - Snead, Jennifer (Mémoires du livre / Studies in Book Culture, 2015)
This article describes the editorial practices that Jonathan Edwards and John Wesley brought to their respective editions of The Life of David Brainerd, explains how those practices were informed by their opposing theological stances towards salvation, and traces the circulation and reception of each edition back to those theological stances. Finally, the article invokes classic models of the methodology of book history and recent work on the circulation of nineteenth-century evangelical publications, arguing that an understanding of the kind of theological editing eighteenth-century figures like Edwards and Wesley took can better help us to articulate nineteenth- and twentieth- (and twenty-first) century attitudes and assumptions about agency and material texts.